2016
DOI: 10.1111/aab.12304
|View full text |Cite
|
Sign up to set email alerts
|

Sporisorium scitamineum colonisation of sugarcane genotypes susceptible and resistant to smut revealed by GFP‐tagged strains

Abstract: Sporisorium scitamineum is the causal agent of sugarcane smut disease. The fungus establishes a biotrophic interaction with sugarcane tissues, and unlike smut fungi of other monocot hosts, the primary meristem of sugarcane plants develops a whip-like structure instead of a tumour-like galls emerging from floral structures (tassels and ears). We examined (GFP)-tagged S. scitamineum infecting tissues of three sugarcane genotypes with distinct responses to smut (susceptible, intermediate resistant and resistant).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…It was reported that severe smut outbreak in the Caribbean has created an impact amongst cane growers and sugar industry. Consequently, the plantations are undertaking different smut management practices such as continued monitoring and rouging of smut affected stools, hot water treatment (at 50°C for 2 hours for initial seed cane nursery) of seed sets, chemical treatment of sets, use of resistant varieties, and avoidance of ratooning of affected fields (Abdou et al, 1990;Wada et al, 1999;Abera et al, 2009;Firehunet al, 2009;Mansour et al, 2016;Carvalho et al, 2016;Sánchez-Elordi et al, 2016 andLiu et al, 2017) Due to their core role in plant health, reactive oxygen species (ROS) and antioxidants Sutherland (1991) and Levine et al (1994) have shown a major role in plant pathogen interactions (Galal and Abdou, 1996;Adam et al, 2000;EL-Ashmony et al, 2017). Both acetic acid and hydrogen peroxide reacted as bactericides and fungicides against many phytopathogenic bacteria and fungi (Narcisoet al, 2007 andOsórioet al, 2013;Ayoub et al, 2017 and).…”
mentioning
confidence: 99%
“…It was reported that severe smut outbreak in the Caribbean has created an impact amongst cane growers and sugar industry. Consequently, the plantations are undertaking different smut management practices such as continued monitoring and rouging of smut affected stools, hot water treatment (at 50°C for 2 hours for initial seed cane nursery) of seed sets, chemical treatment of sets, use of resistant varieties, and avoidance of ratooning of affected fields (Abdou et al, 1990;Wada et al, 1999;Abera et al, 2009;Firehunet al, 2009;Mansour et al, 2016;Carvalho et al, 2016;Sánchez-Elordi et al, 2016 andLiu et al, 2017) Due to their core role in plant health, reactive oxygen species (ROS) and antioxidants Sutherland (1991) and Levine et al (1994) have shown a major role in plant pathogen interactions (Galal and Abdou, 1996;Adam et al, 2000;EL-Ashmony et al, 2017). Both acetic acid and hydrogen peroxide reacted as bactericides and fungicides against many phytopathogenic bacteria and fungi (Narcisoet al, 2007 andOsórioet al, 2013;Ayoub et al, 2017 and).…”
mentioning
confidence: 99%
“…Up-regulation of energy-related pathways is a conserved response to demands of biotic stresses, such as the synthesis of secondary metabolites (Less et al, 2011;Rojas et al, 2014). Even in sugarcane genotypes resistant to smut, i. e. those that do not emit whip, S. scitamineum colonization is detected (Carvalho et al, 2016) potentially interfering with carbon allocation. In addition, increased energetic metabolism network may also imply that stems reduce sucrose accumulation, one of the smut susceptible symptoms yet not investigated in resistant genotypes colonized by smut.…”
Section: Discussionmentioning
confidence: 99%
“…M. Piepenbr., M. Stoll & Oberw is the causal agent of sugarcane smut, one of the major diseases that affect the culture worldwide (Sundar et al, 2015), featuring a biotrophic lifestyle with inter-or intracellular growth (Carvalho et al, 2016;Stoll et al, 2005). The presence of the fungus in the plant leads to the development of a long structure like a "whip" in susceptible varieties at the apex of the apical or lateral meristems (Figure 1A, B;Sundar et al, 2012).…”
Section: Sugarcane and The Smut Diseasementioning
confidence: 99%
See 2 more Smart Citations